The Use of Chained Picture as Media to Improve Students Writing Skill of Narrative Text - Ratna Sari, Dewi; Muamar Chadafi (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The background of the research in this study is based on the phenomenon of students’ difficulties in learning to write English narrative texts. To improve the writing of narrative texts, teachers need strategies or media so that students are happy and easy to write. Picture chain is one media that aims to improve students’ narrative text writing skills. The research uses Classroom Action Research. Classroom action research is a reflective study conducted by the teacher to get a solution until it can be solved. The research was carried out at SMP plus Mamba’ul Hisan for the 2021/2022 academic year. Data analysis shows significant differences in student learning outcomes in the pre-cycle, cycle I, and cycle II, around 55,5%%, 64.5%, and in the second cycle, 74.75% for the second cycle. It shows that students’ achievement in writing narrative texts increases.